Knowledge Transfer Programme of Neurotechnology for Community - Universiti Malaysia, Sarawak (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Since 2009, at Faculty of Cognitive Sciences and Human Development, we have conducted a series of neurofeed-back training sessions for many case studies especially in intellectual disor-ders such as attention deficit or hyper-activity disorder (ADD/ADHD), autism, epilepsy disorder, slow learners and other behavioral studies related to cog-nitive neuroscience. This has been reported in many reports and international conference proceed-ing and journal. We won gold medal for Neurofeedback research at SIIF, Korea 2011, bronze medal for neurofeedbak training for disabled child at UNIMAS R & D expo. We also won silver medal for Neuro-feedback device for disable child at ITEX 2010, Innovation, Invention Tech-nology Exhibition 2010, KLCC, Kuala Lumpur 14 – 16 May 2010.